1998
DOI: 10.1200/jco.1998.16.9.2906
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic isolated limb perfusion for localized, high-risk limb melanoma: results of a multicenter randomized phase III trial. European Organization for Research and Treatment of Cancer Malignant Melanoma Cooperative Group Protocol 18832, the World Health Organization Melanoma Program Trial 15, and the North American Perfusion Group Southwest Oncology Group-8593.

Abstract: Prophylactic ILP with melphalan cannot be recommended as an adjunct to standard surgery in high-risk primary limb melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(60 citation statements)
references
References 21 publications
2
56
0
2
Order By: Relevance
“…Isolated limb perfusion (ILP) is an attractive treatment modality for multiple melanoma in-transit metastases 12,13 . Melphalan is used as the standard chemotherapeutic drug in ILP, with complete response rates of 40-50 per cent 14 ; however, response rates of bulky melanoma lesions have been disappointing owing to poor drug uptake by the tumour, similar to results for advanced soft tissue sarcomas 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Isolated limb perfusion (ILP) is an attractive treatment modality for multiple melanoma in-transit metastases 12,13 . Melphalan is used as the standard chemotherapeutic drug in ILP, with complete response rates of 40-50 per cent 14 ; however, response rates of bulky melanoma lesions have been disappointing owing to poor drug uptake by the tumour, similar to results for advanced soft tissue sarcomas 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this cooperative study group concluded that prophylactic isolated limb perfusion with melphalan could not be recommended as standard therapy for high-risk primary melanoma of the extremities [370].…”
Section: A Hauschildmentioning
confidence: 99%
“…The largest adjuvant study on local hyperthermic limb perfusion with melphalane was a project of the North American Perfusion Group (NAPG), the EORTC, and the WHO. The results showed a decreased incidence of locoregional metastasis but no OS benefit compared to the control group [31]. This treatment with a high toxicity should be restricted to non-resectable in-transit metastasis and not be used as an adjuvant therapy anymore.…”
Section: Hyperthermic Limb Perfusionmentioning
confidence: 92%